Neural mechanisms of emotion regulation in childhood anxiety. (10th October 2012) - Hum, Kathryn M.; Manassis, Katharina; Lewis, Marc D.
<x xml:space="preserve">Abstract</x> Background: The present study was designed to examine the cortical processes that mediate cognitive regulation in response to emotion‐eliciting stimuli in anxious children. Methods: Electroencephalographic (EEG) activity was recorded from clinically anxious children (n = 29) and typically developing children (n = 34). Event‐related potential components were recorded while children performed a go/no‐go task using facial stimuli depicting angry, calm, and happy expressions. Results: Anxious children had significantly greater posterior P1 and frontal N2 amplitudes, components associated with attention/arousal and cognitive control, respectively, than typically developing children. Anxious children also had significantly greater error‐related negativities and correct‐response negativities relative to typically developing children. For the anxious group only, there were no differences in neural activation between face (emotion) types or trial (Go vs. No‐go) types. A regression analysis revealed that No‐go N2 amplitudes for calm faces predicted self‐reported anxiety levels. Conclusions: Anxious children appeared to show increased cortical activation regardless of the emotional content of the stimuli. Anxious children also showed greater medial‐frontal activity regardless of task demands and response accuracy. Taken together, these findings suggest indiscriminate cortical processes that may underlie the hypervigilant regulatory style seen in clinically anxious individuals.